Victimization of police officers in the state of Pará (Brazil) in 2019 (Research, Society and Development, 2020)
This paper aims to describe the victimization of police officers in the state of Pará seeking to analyze data on police officers murder, which occurred from January 2019 to December 2019, seeking to understand what factors may be linked to the occurrence of these events. The data were made available by the Secretariat for Intelligence and Crime Analysis and Homicide Department. During this period, 28 military police officers were killed, 17 (60.7%) in municipalities in the Metropolitan Region of Belém and 11 (39.3%) in the interior of the state. Of the total deaths, 21 (75.0%) were registered as homicide and 7 (25.0%) as robbery. In conclusion, low wages and the need to supplement income outside working hours are factors that contribute to the increase in the risks to which they are subjected. It is suggested that the increase in public policies that bring them better living and working conditions, may reduce their vulnerabilities and victimization.